Contextual barriers and enablers to establishing an addiction-focused consultation team for hospitalized adults with opioid use disorder - Sandra K. Evans; Allison J. Ober; Ariella R. Korn; Alex Peltz; Peter D. Friedmann; Kimberly Page; Cristina Murray-Krezan; Sergio Huerta; Stephen J. Ryzewicz; Lina Tarhuni; Teryl K. Nuckols; Katherine E. Watkins; et al. (Addiction Science & Clinical Practice, 2024)
Abstract Background Hospitalization presents an opportunity to begin people with opioid use disorder (OUD) on medications for opioid use disorder (MOUD) and link them to care after discharge; regrettably, people admitted to the hospital with an underlying OUD typically do not receive MOUD and are not connected with subsequent treatment for their condition. To address this gap, we launched a multi-site randomized controlled trial to test the effectiveness of a hospital-based addiction consultation team (the Substance Use Treatment and Recovery Team (START)) consisting of an addiction medicine specialist and care manager team that provide collaborative care and a specified intervention to people with OUD during the inpatient stay. Successful implementation of new practices can be impacted by organizational context, though no previous studies have examined context prior to implementation of addiction consultation services (ACS). This study assessed pre-implementation context for implementing a specialized ACS and tailoring it accordingly. Methods We conducted semi-structured interviews with hospital administrators, physicians, physician assistants, nurses, and social workers at the three study sites between April and August 2021 before the launch of the pragmatic trial. Using an analytical framework based on the Consolidated Framework for Implementation Research, we completed a thematic analysis of interview data to understand potential barriers or enablers and perceptions about acceptability and feasibility. Results We interviewed 28 participants across three sites. The following themes emerged across sites: (1) START is an urgently needed model for people with OUD; (2) Intervention adaptations are recommended to meet local and cultural needs; (3) Linking people with OUD to community clinicians is a highly needed component of START; (4) It is important to engage stakeholders across departments and roles throughout implementation. Across sites, participants generally saw a need for change from usual care to support people with OUD, and thought the START was acceptable and feasible to implement. Differences among sites included tailoring the START to support the needs of varying patient populations and different perceptions of the prevalence of OUD. Conclusions Hospitals planning to implement an ACS in the inpatient setting may wish to engage in a systematic pre-implementation contextual assessment using a similar framework to understand and address potential barriers and contextual factors that may impact implementation. Pre-implementation work can help ensure the ACS and other new practices fit within each unique hospital context.